Working with Aboriginal Women: Applying Feminist Therapy in a Multicultural Counselling Context - Malone, Judi L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Counsellor education for working with Aboriginal women must address both culture and gender issues and this may be done by applying feminist theory within a multicultural counselling perspective. This paper explores these perspectives, their application to these women, and specific counsellor education considerations. Issues particular to Aboriginal women are discussed in addition to factors for integrating feminism and multicultural counselling within this context. Once counsellors have an increased awareness of these factors, they may become more effective cross-cultural and feminist counsellors for Aboriginal women.